PENGARUH PROFITABILITAS, SOLVABILITAS DAN UKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2018 – 2020 - Irene Alda Uli Siregar; Lorina Siregar Sudjiman (Jurnal Ekonomis, 2021)
This study aims to determine the effect of profitability, solvency and firm size on audit report delays in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The samples used as many as 24 companies with purposive sampling technique. This study uses secondary data that is processed using the SPSS application. The analysis technique used is multiple linear regression analysis. The results showed that profitability and firm size had a negative effect on audit report lag, while solvency had a positive effect on audit report lag.